2007
DOI: 10.1016/j.bbrc.2007.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II binds to SHP2 and this interaction is regulated by HSP70 levels

Abstract: The protein tyrosine phosphatase SHP2 is a positive effector of EGFR signaling. To improve our understanding of SHP2's function, we searched for additional binding proteins of SHP2. We found that Annexin II is an SHP2 binding protein. Physical interactions of SHP2 with Annexin II were confirmed in vivo. Furthermore, binding of SHP2 with Annexin II was regulated somewhat by EGF treatment and the extracellular Ca 2+ chelator, EGTA. Previously, we reported that HSP70 levels can influence the binding of SHP2 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition, some phosphatases are preferentially localized in lipid domains [47], and thus could dephosphorylate AnxA2 at this stage. The calcium-sensitive phosphatase Src homology 2 (SH2)-containing protein tyrosine phosphatase (Shp2) is an interesting candidate because Shp2 can interact with AnxA2 in the presence of cholesterol [48,49], Shp2 is highly specific for phosphorylated AnxA2-Tyr23 [50] and Shp2 is expressed in chromaffin cells.…”
Section: Regulation Of the Anxa2-tyr23 Phosphorylation/dephosphorylat...mentioning
confidence: 99%
“…In addition, some phosphatases are preferentially localized in lipid domains [47], and thus could dephosphorylate AnxA2 at this stage. The calcium-sensitive phosphatase Src homology 2 (SH2)-containing protein tyrosine phosphatase (Shp2) is an interesting candidate because Shp2 can interact with AnxA2 in the presence of cholesterol [48,49], Shp2 is highly specific for phosphorylated AnxA2-Tyr23 [50] and Shp2 is expressed in chromaffin cells.…”
Section: Regulation Of the Anxa2-tyr23 Phosphorylation/dephosphorylat...mentioning
confidence: 99%
“…This receptor of plasminogen activator at the membrane surface interacts with receptor tyrosine kinases like EGFR, insulin receptor (IR), insulin growth factor receptor (IGFR), and non-receptor tyrosine kinases such as Focal adhesion kinase and Src, which helps in cell signaling, angiogenesis, matrix degradation, invasion, and metastasis of cancer cells. Earlier reports have also shown that involvement of AnxA2 in internalization and sorting of EGFR in early endosomes after ligand activation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…The cell surface associated AnxA2 heterotetramer, is a receptor for both plasminogen and tissue type plasminogen activator (tPA) and acts as a catalytic center for the activation of plasminogen to plasmin [27,28] which helps in invasion and metastasis of cancer cells [18,27]. The membrane associated AnxA2 interacts with RTKs such as like insulin receptor (IR), insulin-like growth factor receptor (IGFR) and non-receptor tyrosine kinases such as focal adhesion kinase (FAK) and Src [29][30][31][32][33]. AnxA2 acts as a key scaffolding protein in anchoring and transportation of several proteins within plasma membrane as well as from cytosol to the plasma membrane, and contributes to cell signaling, angiogenesis and matrix degeneration [33][34][35].…”
Section: Introductionmentioning
confidence: 99%